The Iranian Talmud : reading the Bavli in its Sasanian context - Secunda, Shai (Divinations., 2014)
This book reexamines the Babylonian Talmud - one of Judaism's most central texts - in the light of Persian literature and culture, providing an accessible overview to the vibrant world of pre-Islamic Iran that shaped the Bavli.